A new upper bound for sets with no square differences. Issue 8 (30th August 2022) - Bloom, Thomas F.; Maynard, James
Abstract : We show that if A{1, …, N} has no solutions to a-b=n^2 with a, bA and n≥ 1, then \[ A vert N(N)^cN \] for some absolute constant c>0 . This improves upon a result of Pintz, Steiger, and Szemerédi.